Hybrid phosphorus–viologen dendrimers as new soft nanoparticles: design and properties. Issue 16 (4th June 2021) - Majoral, Jean-Pierre; Zablocka, Maria; Ciepluch, Karol; Milowska, Katarzyna; Bryszewska, Maria; Shcharbin, Dzmitry; Katir, Nadia; El Kadib, Abdelkrim; Caminade, Anne-Marie; Mignani, Serge
Abstract : Design of new families of dendritic soft nanoparticles constituted of phosphorus, viologen and carbosilane fragments and their properties as nanomaterials and applications in biology. Abstract : Various dendritic structures have been prepared during the last few decades and their properties have been emphasized in a number of reviews. Among these macromolecular structures, those incorporating phosphorus units – phosphorus dendrimers – or viologen linkages – viologen dendrimers – stand as the most promising in different fields spanning from chemistry, materials science to biology and nanomedicine. The association of the two complementary phosphorus and viologen structures resulted in a nascent family of structures referred to as "mixed" hybrid phosphorus–viologen dendrimers. In light of their specific properties, it is of interest to illustrate the conceptual preparation of not only a variety of sophisticated hybrid viologen–phosphorus dendrimers including classical dendrimers, but also other kinds of mixed macromolecules such as macromolecular asterisks, onion peel structures and covalent polydendrimer frameworks. Some preliminary results concerning the biological properties of these nano-objects as well as their use for the construction of organic–inorganic hybrid materials are presented.